2016
DOI: 10.1111/ens.12221
|View full text |Cite
|
Sign up to set email alerts
|

Cornicle secretions of Uroleucon nigrotuberculatum (Homoptera: Aphididae) as the last bullet against lady beetle larvae

Abstract: Aphids have evolved various defense strategies against natural enemies, including secretions from their cornicles. We assessed the defensive function of cornicle secretions by the goldenrod aphid, Uroleucon nigrotuberculatum (Olive), against larvae of the lady beetles Coccinella septempunctata bruckii Mulsant and Propylea japonica (Thunberg) (Coleoptera: Coccinellidae). The aphid secreted red droplets from its cornicles when attacked by the larvae. Two‐thirds of the C. septempunctata bruckii larvae and 46.7% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Chemically, some aphids produce cornicle secretions bearing alarm pheromones that alert conspecifics of impending danger (Vandermoten et al, 2012). Cornicle secretions can also coat the rostrum and mouthparts of certain predators, preventing them from moulting or feeding (Barry & Ohno, 2016). While first‐line responses can be successful, they are often bypassed by some aphid parasitoids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemically, some aphids produce cornicle secretions bearing alarm pheromones that alert conspecifics of impending danger (Vandermoten et al, 2012). Cornicle secretions can also coat the rostrum and mouthparts of certain predators, preventing them from moulting or feeding (Barry & Ohno, 2016). While first‐line responses can be successful, they are often bypassed by some aphid parasitoids.…”
Section: Introductionmentioning
confidence: 99%
“…Cornicle secretions can also coat the rostrum and mouthparts of certain predators, preventing them from moulting or feeding (Barry & Ohno, 2016). While first-line responses can be successful, they are often bypassed by some aphid parasitoids.…”
Section: Introductionmentioning
confidence: 99%
“…Aphid cornicle secretions are composed largely of triglycerides and function as a fast-drying liquid wax with strongly adhesive properties (Callow et al , 1973), although more recent analyses have revealed greater chemical complexity (Alfaress et al , 2016). Droplets of cornicle secretion can permanently seal the mouthparts of smaller predators or otherwise ensnare them (Butler & O'Neil, 2006; Barry & Ohno, 2016), foul parasitoid antennae and force wasps to engage in an extended period of grooming, and even result in parasitoid death when wasps become permanently stuck to the aphid (Rasekh et al , 2010 a ). However, the secretion of cornicle droplets can result in various fitness costs for the aphid.…”
Section: Introductionmentioning
confidence: 99%